Coping with strategic uncertainty: framework development and scenario derivation for a JV decision in the Russian truck industry. Issue 4 (8th August 2016) - Winkler, Jens; Moser, Roger
Abstract : Purpose: Across country and regional borders firms are faced with the question whether to address individual markets on a stand-alone basis or cooperatively. In order to support such strategic decisions we develop a decision framework accounting for the most relevant market dynamics affecting JV decisions, particularly in the truck industry. Moreover, we apply the framework to an expert Delphi and scenario approach in order to back a Western OEM's JV decision in the truck industry in Russia. Based on country-specific projections structured along the globally applicable decision framework, we serve executives' individual information demand in an institutionally unique emerging market environment. Design/methodology/approach: Online real-time expert Delphi study; scenario analysis; expert workshops. Findings: Among other insights, the results predict hard times for Russian OEMs as they will likely face strong foreign competition leading to decreased sales volumes and market shares. While some experts doubt the survival of several Russian truck manufacturers, the Delphi sheds light on possible strategic responses including consolidation, cooperation, or focusing on new markets. Based on the Delphi results and an additional expert workshop we draw multiple scenarios addressing particularly uncertain aspects of the industry's development and their likely impact on the key stakeholder groups Originality/value: Although there are some studies following a similar methodological approach as ours (e.g. von der Gracht and Darkow, 2010; Gnatzy and Moser, 2012), we break new ground in developing a JV-dedicated decision framework and applying it to a special emerging market industry setup.